2021
DOI: 10.1371/journal.pone.0246417
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, physiological parameters, and transcript levels of lipid metabolism-related genes in hybrid yellow catfish (Tachysurus fulvidraco ♀ × Pseudobagrus vachellii ♂) fed diets containing Siberian ginseng

Abstract: In high-density aquaculture, fish health can suffer because of excessive feeding, which causes fatty liver disease. Siberian ginseng (Acanthopanax senticosus) has been used as a feed additive to promote animal growth, immunity, and lipid metabolism. In this study, we explored the effects of A. senticosus on the physiology of hybrid yellow catfish (Tachysurus fulvidraco ♀ × Pseudobagrus vachellii ♂). A control group and five groups fed diets containing A. senticosus (0.5, 1, 2, 4, and 8 g A. senticosus/kg feed)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Additionally, the effects of dietary Leucine, threonine, and tryptophan were investigated on various growth performance parameters, including muscle growth and protein synthesis and degradation-related signaling pathways, in hybrid Bagrid catfish (P. vachelli ♀× L. longirostris ♂) [122,123]. Li et al [124] explored the growth performance, physiological parameters, and transcript levels of lipid metabolism-related genes in hybrid yellow catfish (P. fulvidraco ♀, P. vachelli ♂) when fed diets containing Siberian ginseng. The results indicated that an appropriate dietary supplementation rate of 2-4 g/kg of Siberian ginseng can influence the regulation of fat metabolism and promote the growth of hybrids [124].…”
Section: Metabolic Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the effects of dietary Leucine, threonine, and tryptophan were investigated on various growth performance parameters, including muscle growth and protein synthesis and degradation-related signaling pathways, in hybrid Bagrid catfish (P. vachelli ♀× L. longirostris ♂) [122,123]. Li et al [124] explored the growth performance, physiological parameters, and transcript levels of lipid metabolism-related genes in hybrid yellow catfish (P. fulvidraco ♀, P. vachelli ♂) when fed diets containing Siberian ginseng. The results indicated that an appropriate dietary supplementation rate of 2-4 g/kg of Siberian ginseng can influence the regulation of fat metabolism and promote the growth of hybrids [124].…”
Section: Metabolic Nutritionmentioning
confidence: 99%
“…Li et al [124] explored the growth performance, physiological parameters, and transcript levels of lipid metabolism-related genes in hybrid yellow catfish (P. fulvidraco ♀, P. vachelli ♂) when fed diets containing Siberian ginseng. The results indicated that an appropriate dietary supplementation rate of 2-4 g/kg of Siberian ginseng can influence the regulation of fat metabolism and promote the growth of hybrids [124]. In terms of the mechanism of fatty liver disease, Qiang et al [125] found that the group with a high dietary lipid level (17.08%) exhibited fatty liver symptoms, such as lower growth, higher hepatic triglyceride and cholesterol contents, and larger lipid droplets in liver tissue, compared to a normal-fat diet group (8.87% dietary lipid level).…”
Section: Metabolic Nutritionmentioning
confidence: 99%
“…On the other hand, driven by declining costs, RNA-seq is becoming increasingly accessible to labs with modest resources; and as a result, it is being employed on an ever-expanding catalog of non-model organisms, pervading the fields of agriculture, aquaculture, ecology, and environment. A very short list of recent studies include: environmental stress response in sea-trout [ 3 ], coral [ 4 ], ryegrass [ 5 ], pigeonpea [ 6 ], tiger barb [ 7 ]; immune response to parasites and pathogens in guppy [ 8 ], eel [ 9 ], silkworm [ 10 ], peanut [ 11 ], sunflower [ 12 ]; mechanisms of phenotypic divergence in hares [ 13 ], bats [ 14 ], grass carps [ 15 ]; effect of diet in the growth and development in shrimp [ 16 ], yellow perch [ 17 ], mandarin fish [ 18 ], grenadier anchovy [ 19 ], catfish [ 20 ], tilapia [ 21 ], bass [ 22 ]. It is only likely that RNA-seq will continue to rapidly proliferate while high-quality reference databases grow at a slow pace.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, driven by declining costs, RNA-seq is becoming increasingly accessible to labs with modest resources; and as a result, it is being employed on an everexpanding catalog of non-model organisms, pervading the fields of agriculture, aquaculture, ecology, and environment. A very short list of recent studies include: environmental stress response in sea-trout [3], coral [4], ryegrass [5], pigeonpea [6], tiger barb [7]; immune response to parasites and pathogens in guppy [8], eel [9], silkworm [10], peanut [11], sunflower [12]; mechanisms of phenotypic divergence in hares [13], bats [14], grass carps [15]; effect of diet in the growth and development in shrimp [16], yellow perch [17], mandarin fish [18], grenadier anchovy [19], catfish [20], tilapia [21], bass [22]. It is only likely that RNA-seq will continue to rapidly proliferate while high-quality reference databases grow at a slow pace.…”
Section: Introductionmentioning
confidence: 99%